Teologia misji i ruch misyjny w nauczaniu wczesnego Kościoła Jezusa Chrystusa Świętych w Dniach Ostatnich (mormonów) - Anoszko, Sergiusz (Annales Missiologici Posnanienses, 2023)
Mormons are particularly concerned about missionary work, putting much effort into converting non-Mormons into their faith. The proposed text attempts to focus on the goals of the missionary activity of this quasi-Christian new religious movement, to explain the processes by which the Mormons formed their view of conversion and how to achieve them in daily life during missionary work at the early stages of the history of the denomination. An analysis of the idea of mission in the teaching and practice of the Church of Joseph Smith allows us to gain an understanding of the general theological and anthropological principles of modern Mormonism.